Répondre :
Réponse :
Explications étape par étape
A = 10 - ( x + 3 ) + ( - 3x + 6 ) - ( x - 3 ) = -1 * ( x - 3 ) = - x + 3
⇔ A = 10 - x - 3 - 3x + 6
⇔ A = - 4x + 13 regrouper les termes
B = 2 ( 5 + 2x ) - ( -7 - 7x ) 2 ( 5 + 2x ) = 10 + 4 x distributivité
⇔ B = 10 + 4x + 7 + 7x - ( -7 - 7x ) = - 1 * (-7 - 7x ) = 7 + 7x distributivité
⇔ B = 11 x + 17
Bonsoir,
A = 10 - (x + 3) + (-3x + 6)
= 10 - x - 3 - 3x + 6
= -4x + 13
B = 2(5 + 2x) - (-7 - 7x)
= 10 + 4x + 7 + 7x
= 11x + 17
Voilà ! (l’énoncé n’est pas clair, dis moi si c’est pas ça)
A = 10 - (x + 3) + (-3x + 6)
= 10 - x - 3 - 3x + 6
= -4x + 13
B = 2(5 + 2x) - (-7 - 7x)
= 10 + 4x + 7 + 7x
= 11x + 17
Voilà ! (l’énoncé n’est pas clair, dis moi si c’est pas ça)